Surgical complications in colorectal cancer patients. (July 2020) - Pak, Haleh; Maghsoudi, Leila Haji; Soltanian, Ali; Gholami, Farshid
Abstract: Background: Advancements in diagnostic and therapeutic sciences have allowed early diagnosis and treatment of cancer. Colorectal cancer is one of the most commonly reported cancers, particularly in elderly patients. Methods: Open and laparoscopic surgeries are used for the removal of the tumor, along with chemotherapy, depending on the stage of cancer. However, colorectal cancer surgery is associated with a great number of complications, that affect the efficacy of the surgery and overall health and survival of the patient. Results: Prevalence of these complications have shown discrepancies depending on the condition of the patient and disease and surgical skills of the surgeon. Preoperative evaluation, intraoperative care and postoperative measures can reduce the incidence of these complications. Conclusion: This review highlights some frequently reported complications associated with colorectal cancer surgery, their risk factors and subsequent therapeutic measures to treat them. Highlights: Colorectal cancer is one of the most commonly reported cancers, particularly in elderly patients. Numerous postoperative complications are reported that can significantly lead to morbidities, prolonged hospital stay and even mortality. Management of these adverse effects can be beneficial for overall survival rate and improvement in the quality of life.